Once more into the crypt: A geocritical approach to Luis Buñuel’s Las Hurdes: Tierra sin pan - Kozey, Christopher (Studies in Spanish & Latin American Cinemas, 2015)
Abstract Luis Buñuel’s short documentary film, Las Hurdes: Tierra sin pan/Las Hurdes: Land without Bread (1933) has long frustrated critics, who have variously categorized it as a socialist-realist call to arms, a brutal parody of ethnography and a flirtation with sadism. Some question whether the film is a documentary at all. By examining the film in light of not only its historically immediate predecessors, but also an often-neglected one – Lope de Vega’s play, Las Batuecas del Duque de Alba/The Duke of Alba’s Las Batuecas (Lope de Vega, 1604–1614) – I will account for the facet of Las Hurdes that these disparate characterizations fail to include. To do so, this investigation engages in what Bertrand Westphal calls ‘geocriticism’, a critical practice that ‘studies the literary stratifications of referential space’. Here, the space in question is the valley of Las Batuecas/Las Hurdes, and the key strata are Lope’s play and Buñuel’s film the former text casts the region as a ‘crypt space’ for Castile, and the latter recapitulates and critiques that role in a new temporal context. By scrutinizing these textual reconfigurations of the region as part of the same broader phenomenon, I will elucidate the aesthetically and politically contentious relationship of Las Hurdes’ diegetic content to its human and geographical referents.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9zbGFjLjEyLjMuMjk1XzE